MEDIA PEMBELAJARAN INTERAKTIF PENGENALAN HURUF DALAM BAHASA INDONESIA MENGGUNAKAN VOICE RECOGNITION BERBASIS ANDROID - Sukmawaty; Syaiful Rahman; Junaedy (STMIK KHARISMA Makassar, 2017)
The purpose of this research is to make interactive learning media for learning alphabet in Indonesian language using voice regocnition on android. This research based on the problem of how to design and build a learning media that can meet two types of children in learning alphabet. The first one is visual learner and auditory learner. To support this research, writer used Android Studio software that can produce an interactive application, and runs well in smartphone that using android as operation system. For testing method, writer was using black box testing. The results of this research are writer can design and build a learning media for learning alphabet for children by using voice recognition using the Android Studio software to produce interactive applications and can meet the two types of children in learning alphabet.